Implementation Of Stunting Reduction Acceleration Policy In Ponorogo Regency - Faradiba Aisyah (Journal Of Social Science (JoSS), 2023)
The study aims to explain the implementation of the policy of accelerating the reduction of stunting in the Ponorogo district, to know the process of implementation, supportive factors as well as inhibitory factors. As for the method used in this research, the method is descriptive. The results of this study show that the implementation process of the Ponorogo Government Regulation No. 33 of 2022 on the Acceleration of Stunting Decrease at the Village Level is through phases of interpretation, organization, and application. From the results of the study of the implementation phase of the policy, it is known that implementation of the stunting regulations has been optimum by showing a decrease in the prevalence of stunting in Ponorogo district, which in 2021 reached a figure of 14.92% while in 2022 at 13.69%. Successful implementation of the Ponorogo Stunting Regulation No. 33 of 2022 on the Acceleration of Stunting Decrease at the Village Level is seen from the implementation process as well as the presence of supportive factors in implementing the stunting regulation, although there are also obstacles in its implementation.